Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Section 1.3 - Algebraic Expressions - 1.3 Exercises: 92

Answer

$3x^{-1/2}+4x^{1/2}+x^{3/2}=\dfrac{1}{\sqrt{x}}(x+3)(x+1)$

Work Step by Step

$3x^{-1/2}+4x^{1/2}+x^{3/2}$ Take out common factor $x^{-1/2}$: $3x^{-1/2}+4x^{1/2}+x^{3/2}=x^{-1/2}(3+4x+x^{4/2})=...$ $...=x^{-1/2}(x^{2}+4x+3)=...$ Factor the expression inside the parentheses: $...=\dfrac{1}{\sqrt{x}}(x+3)(x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.